Analysis of Surface Water Quality of Four Rivers in Jayapura Regency, Indonesia: CCME-WQI Approach - Rosye Hefmi Rechnelty Tanjung (Polish Society of Ecological Engineering (PTIE), 2022)
In Indonesia, the river water quality has been determined based on Government Regulation of the Republic of Indonesia No. 22 of 2021. This study aimed to determine the quality of surface water from the Damsari, Jabawi, Kleblow, and Komba Rivers in Jayapura Regency based on the monitoring data from 2016 to 2019. The CCME-WQI method is used to determine the status of rivers based on river water quality standards (class 1 to class 4). The results of the study showed that the parameters of water temperature, TDS, pH, NH3, NO3-, SO4-2, surfactant, oil/grease, Cr-(IV), Mn, Fe, Fecal Coliform, and Total Coliform were still in accordance with the quality standard. Meanwhile, TSS, COD, BOD, Total Phosphate, Hg, and Ni have exceeded the water quality standard, where the dominant pollutant source is an anthropogenic waste. On the basis of the WQI average value, the four rivers are not suitable as a source of drinking water (Poor-Marginal; 41.33 – 58.25). The Jabawi River can be used as a recreational facility, but it must be under special management (Fair; 69.75), while the other three rivers are not suitable (Marginal; 52.00 – 61.67). The Jabawi and Komba Rivers are in the Fair category (75.50 and 69.33) to support aquatic life, while the Damsari and Kleblow Rivers are in the Marginal category (59.00 and 61.25). The water quality of the four rivers is very good and suitable to be used as a water source for irrigation (Good category; 80.00 – 88.00). The strategies for controlling river water pollution and increasing the role of the government, stakeholders, and the community are needed.